Revisiting Brain Tuberous Sclerosis Complex in Rat and Human: Shared Molecular and Cellular Pathology Leads to Distinct Neurophysiological and Behavioral Phenotypes - Kútna, Viera; O'Leary, Valerie B; Newman, Ehren; Hoschl, Cyril; Ovsepian, Saak V (Neurotherapeutics, 2021)
Tuberous sclerosis complex (TSC) is a dominant autosomal genetic disorder caused by loss-of-function mutations in TSC1 and TSC2, which lead to constitutive activation of the mammalian target of rapamycin C1 (mTORC1) with its decoupling from regulatory inputs. Because mTORC1 integrates an array of molecular signals controlling protein synthesis and energy metabolism, its unrestrained activation inflates cell growth and division, resulting in the development of benign tumors in the brain and other organs. In humans, brain malformations typically manifest through a range of neuropsychiatric symptoms, among which mental retardation, intellectual disabilities with signs of autism, and refractory seizures, which are the most prominent. TSC in the rat brain presents the first-rate approximation of cellular and molecular pathology of the human brain, showing many instructive characteristics. Nevertheless, the developmental profile and distribution of lesions in the rat brain, with neurophysiological and behavioral manifestation, deviate considerably from humans, raising numerous research and translational questions. In this study, we revisit brain TSC in human and Eker rats to relate their histopathological, electrophysiological, and neurobehavioral characteristics. We discuss shared and distinct aspects of the pathology and consider factors contributing to phenotypic discrepancies. Given the shared genetic cause and molecular pathology, phenotypic deviations suggest an incomplete understanding of the disease. Narrowing the knowledge gap in the future should not only improve the characterization of the TSC rat model but also explain considerable variability in the clinical manifestation of the disease in humans.
Keywords: tuberin; Disease Models, Animal; Animals; tuberózní skleróza; hamartoma; Brain; TSC1; TSC2; Rats; neoplasia; refractory epilepsy; Humans; hamartin; Tuberous Sclerosis Complex 1 Protein; TOR Serine-Threonine Kinases; Tuberous Sclerosis; modely nemocí na zvířatech; Phenotype; duševní poruchy; autism spectrum disorders; Tuberous Sclerosis Complex 2 Protein; lidé; fenotyp; mozek; zvířata; Species Specificity; Mental Disorders; druhová specificita; krysa rodu Rattus; mTOR signaling; TOR serin-threoninkinasy